Monitoring the governance of state-owned enterprises: Assessing the impact of corporate governance reforms in Brazil - Daphne Coelho; Thomaz Teodorovicz; André Carlos Martínez Fritscher; Renata Motta Café; Sérgio Lazzarini; Jorge Norio Rezende Ikawa (Inter-American Development Bank (IDB), 2024)
State-owned enterprises (SOEs) are often justified for correcting market failures, providing essential public services, and fulfilling social objectives. Yet, SOEs face unique governance challenges as agency conflicts usually increase with state ownership. This paper examines Brazil's efforts to address agency conflicts in SOEs, including new legislation (Law 13303 of 2016, the "Law on SOEs") establishing stringent criteria for the appointment of executives and for the accountability and a complementary monitoring mechanism known as IG-SEST. Using the difference-in-differences methodology, we assess the impact of those interventions on SOEs profitability and labor productivity. Although no significant effect of the more-stringent governance requirements of the Law on SOEs was detected, the group of federal SOEs, which adopted the IG-SEST monitoring mechanism, significantly increased their profitability compared to similar municipal and state SOEs. Because IG-SEST anchored its indicators in corporate governance parameters specified in the Law on SOEs, this result can be interpreted as potential evidence that institutional changes might require complementary mechanisms for effective implementation. These findings are consistent with previous work suggesting that corporate governance might require broader institutional reforms, including fiscal policies to mitigate government action with a negative effect on the performance and solvency of SOEs.
Keywords: G34; H11; H83; L32; 330; state-owned enterprises; state ownership; state capitalism; corporate governance; corporate governance reform